A profile of Filipino women : their status and role - Rojas-Aleta, Isabel; Silva, Teresita L.; Eleazar, Christine P. (Manila : Philippine Business for Social Progress, 1977)
The purpose of this study is to develop a profile of the status and role of Filipino women in the country's development. The study basically a literature survey of existing materials on Filipino women in various aspects of their lives.
Introduction : summary -- Historical perspective : summary -- Sex role socialization : summary -- Empirical data on the status and role of Filipino women : summary -- V. Legal status -- VI. Women in rural areas -- VII. The Filipino women in cultural minority groups -- VIII. Current activities and programs -- IX. Regional profiles based on emperical data on the status and role of Filipino women -- X. Recommendations -- XI. Implications for action programs
Includes bibliographical references.
Keywords: WOMEN -- FILIPINO; SOCIAL STATE -- PHILIPPINES